This study aims to find out how to prepare muhadtsah teaching materials in first grade Arabic learning at MTS at Darul Qur'an Kubang, Kampar Riau Regency, and how to apply good muhadtsah teaching materials in first grade Arabic learning at MTS at Darul Qu - M. Ripani Saputra (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This study aims to find out how to prepare muhadtsah teaching materials in first grade Arabic learning at MTS at Darul Qur'an Kubang, Kampar Riau Regency, and how to apply good muhadtsah teaching materials in first grade Arabic learning at MTS at Darul Qur'an Kubang. Kampar Riau Regency. and to collect data, the researcher used the interview method, the observation method, and the documentation method. And each of the data collected was analyzed by descriptive analysis, which is an analysis that uses compound words in expanded sentences. The results of this study are: the teaching materials applied to first graders are not all in accordance with their daily lives at the lodge and the conversational teaching methods used for first graders with direct methods are not all used in the target language directly. In its application, the teacher uses Indonesian or OCU language to explain the material and vocabulary. In this education there are many problems, namely the lack of media used by teachers when learning, as well as the lack of first grade students' vocabulary and their courage in muhadatsah, so that they are afraid of mistakes in speaking. To overcome this problem, researchers should suggest compiling appropriate muhadatsah teaching materials in terms of their daily lives at the lodge. and Teaching this muhadtsah directly in accordance with the direct method learning steps coupled with varied media when explaining difficult sentences will be effective for first grade MTS students at Darul Qur'an Kubang, Kampar Riau Regency.